Digital forensic investigation of two-way radio communication equipment and services. (July 2018) - Kouwen, Arie; Scanlon, Mark; Raymond Choo, Kim-Kwang; Le-Khac, Nhien-An
Abstract: Historically, radio-equipment has solely been used as a two-way analogue communication device. Today, the use of radio communication equipment is increasing by numerous organisations and businesses. The functionality of these traditionally short-range devices have expanded to include private call, address book, call-logs, text messages, lone worker, telemetry, data communication, and GPS. Many of these devices also integrate with smartphones, which delivers Push-To-Talk services that make it possible to setup connections between users using a two-way radio and a smartphone. In fact, these devices can be used to connect users only using smartphones. To date, there is little research on the digital traces in modern radio communication equipment. In fact, increasing the knowledge base about these radio communication devices and services can be valuable to law enforcement in a police investigation. In this paper, we investigate what kind of radio communication equipment and services law enforcement digital investigators can encounter at a crime scene or in an investigation. Subsequent to seizure of this radio communication equipment we explore the traces, which may have a forensic interest and how these traces can be acquired. Finally, we test our approach on sample radio communication equipment and services.